Pengaruh Return on asset, ukuran Perusahaan, dan debt to equity ratio terhadap ketepatan waktu pelaporan keuangan perusahaan perbankan yang terdaftar di bursa efek indonesia - Mega Putri T, Mississippi; Natsir, Muhammad; Pasulu, Milka (Jurnal Online Manajemen ELPEI, 2025)
This research is a quantitative research, using secondary data obtained from the Indonesia Stock Exchange (IDX). The population in this study was 45 companies listed on the Indonesia Stock Exchange in 2021-2023. There were 20 companies that met the criteria to be sampled in this company. The analysis technique used in this study was multiple linear regression. The results showed that the Return on Asset and Debt to Equity Ratio variables had a significant effect on the Timeliness of Financial Reporting. Meanwhile, the Company Size variable did not have a significant effect on the timeliness of financial reporting.